PELATIHAN PEMBUATAN CILOK IKAN SERTA ANALISIS USAHANYA - Irine Ike Praptiwi; Maria M.D Widiastuti; Wahida Wahida; Modesta Ranny Maturbongs; Heny V Saiya (Musamus Devotion Journal, 2021)
Fish have high nutritional value and are well consumed by the community,especially children, one of the fish that has a high nutritional content, namely gastorfish (Channa striata), besides containing albumin needed by the body. Thiscommunity service aims to improve the skills of local communities in processingfishery products in the form of Gastor fish and meat into products that have a higherselling value and are more popular with the community, especially children. Thisservice activity lasted for 1 day carried out on Sunday, July 28, 2019, located in oneof the local residents in RT 11 RW 2, Rimba Jaya Village, Merauke Regency. Themethod used in this service activity is in the form of explanations, training in theform of direct practice in making processed fish meat in the form of cilok. Theresponse from the community service participants was quite enthusiastic, theyparticipated in activities from beginning to end and were actively involved in themanufacturing process, to the calculation of business analysis